Tenth Periodic Monitoring Report On The Status Of Management Implementation Plans In Response To Board-Endorsed IEO Recommendations. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2020)
The Tenth Periodic Monitoring Report (PMR) on the Status of Management Implementation Plans (MIPs) in Response to Board-Endorsed Independent Evaluation Office (IEO) Recommendations assesses the progress made over the last year on actions contained in 10 MIPs with open management actions.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet